Pengaruh Kualitas Produk dan Pemasaran Digital terhadap Keputusan Pembelian Pelanggan Kopi Arabika Provinsi DKI Jakarta dengan Harga sebagai Variabel Mediasi - Austin Natama; Ismail Razak; Guswandi (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2025)
This study aims to analyze the influence of product quality and digital marketing on Arabica coffee purchasing decisions in Jakarta, with price as a mediating variable. The method used was a quantitative approach through a survey of 100 respondents, and data analysis using path analysis techniques. The results showed that product quality and digital marketing had a positive and significant effect on price and purchasing decisions. Price was also shown to have a positive influence on purchasing decisions and acted as a mediating variable between product quality and digital marketing on purchasing decisions. These findings suggest that improving quality and appropriate digital marketing strategies can encourage the formation of appropriate price values ​​and support increased purchasing decisions. Therefore, Arabica coffee business actors are advised to maintain product quality and optimize the use of digital channels in their marketing activities.